Towards the development of a pro-environmental strategy for improving catch-and-release behaviour in recreational fisheries "“ a case study on a competitive South African angling body - Mannheim, Samantha L (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2021)
Catch-and-release (C&R) is becoming increasingly popular in recreational fisheries with the potential to contribute towards conserving the oceans limited fish stocks. Several studies have highlighted high rates of mortality and many sub-lethal effects which ultimately have a negative impact on fish population viability. With poorly developed handling practices, the fish that are released suffer the consequences of physical and physiological stress and do not always survive, thus making the ethics of C&R fishing questionable. Many studies have contributed to our understanding of the factors that influence the fate of fish released by anglers. Despite this, few interventions have been able to improve angler C&R behaviour. Pro-environmental behavioural strategies however hold some potential for improving angler C&R behaviour. To test their potential, we partnered with the South African Rock and Surf Super Pro League (RASSPL Africa), the biggest exclusively C&R competitive shore-based angling league in South Africa. The first two years (2013 and 2014) of the partnership were purely focused on building trust and relationships and making observations on angler behaviour. In 2015, we collected baseline data on angler behaviour and fish health during the RASSPL national fishing competition. This was followed by comparable data collection at the following two national competitions in 2016 and 2017 after the introduction of a combination of pro- environmental behaviour interventions, including rule changes, improving angler knowledge, behavioural modelling, rewards, penalties and feedback to improve C&R behaviour. There were significant improvements in angler behaviour, including a decline in total air exposure from 101.93s Â± 64.34 in 2015 to 77.37s Â± 60.52 in 2017 (F(2,618) = 9.27, P < 0.01), and the time taken for an angler to place their fish into a bucket declined from 105.86s Â± 69.47 in 2015 to 23.05s Â± 24.13 in 2017 (F(2,556) = 158.71, P < 0.01). There were also improvements in the health of the fish, with a decline in the blood lactate concentration and mean reflex action mortality predictor (RAMP's) scores for the dominant species, Diplodus capensis (lactate "“ 9.46 Â± 3.80 mmol.l-1 in 2015 and 6.69 Â± 2.99 mmol.l-1 in 2017, RAMP "“ 0.28 Â± 0.22 in 2015 and 0.19 Â± 0.17 in 2017), and Haploblapharus fuscus (lactate "“ 4.25 Â± 1.89 mmol.l-1 in 2015 and 1.76 Â± 0.78 mmol.l-1in 2017, RAMP "“ 0.15 Â± 0.18 in 2015 and 0 Â± 0 in 2017). In 2018, surveys were conducted to gain insight into angler demographics and external (social, economic, cultural and institutional) and internal factors (knowledge and awareness, motivations, attitudes and perceptions) associated with the RASSPL anglers. Surveys were also designed to assist in identifying what components were key drivers behind the angler's behavioural changes. The demographic characteristics of RASSPL anglers were not dissimilar from the general recreational angling public in South Africa, suggesting that this kind of intervention may have potential at a broader scale. In terms of the drivers of behavioural change, the surveys revealed that 68% of respondents strongly agreed that the structural rule changes contributed to their improved behaviour. This was followed by the educational presentations (66% of the respondents) and modelling / demonstrative videos (59% of the respondents). The conservation prizes were considered less effective, with only 27% of anglers strongly agreeing that this intervention improved their C&R behaviour. Overall this study has demonstrated that it is possible to improve the C&R behaviour of anglers in a competitive setting, with the most effective component of the intervention being the use of rule changes (structural approach). These findings suggest that proenvironmental strategies hold potential for improving the C&R behaviour of anglers and the health of released fishes. It is suggested that interventions to improve C&R behaviour should aim to develop long-term relationships, and implement a broad range of well communicated strategies based on reliable data and sound rationality. Key words: marine shore-based fisheries; community engagement; pro- environmental behaviour; behavioural intervention.
Keywords: Fishing -- Environmental aspects -- South Africa; Fishing -- South Africa; Fishers -- Attitudes -- South Africa; Fishers -- Attitudes -- South Africa -- Cast studies; Fishes -- Conservation -- South Africa; Rock and Surf Super Pro League; Southern African Fisheries Ecology Research Lab